Associations of gestational exposure to organophosphate esters with gestational age and neonatal anthropometric measures: The HOME study. (1st January 2023) - Yang, Weili; Braun, Joseph M.; Vuong, Ann M.; Percy, Zana; Xu, Yingying; Xie, Changchun; Deka, Ranjan; Calafat, Antonia M.; Ospina, Maria; Burris, Heather H.; Yolton, Kimberly; Cecil, Kim M.; et al.
Abstract: Organophosphate esters (OPEs) are developmental toxicants in experimental studies of animals, but limited evidence is available in humans. We included 340 mother-infant pairs in the Health Outcomes and Measures of the Environment (HOME) Study (Cincinnati, Ohio, USA) for the analysis. We evaluated gestational exposure to OPEs with gestation age at birth and newborn anthropometric measures. We quantified four OPE urinary metabolites at 16 weeks and 26 weeks of gestation. We extracted gestational age at birth, newborn weight, length, and head circumference from the chart review. We calculated z-scores for these anthropometric measures and the ponderal index. We used multiple informant models to examine the associations between repeated OPE measurements and the outcomes. We used modified Poisson regression to estimate the association of gestational exposure to OPEs with preterm birth. We also explored effect modification by infant sex and the potential mediation effect by the highest maternal blood pressure and glucose levels. We found that bis(2-chloroethyl) phosphate (BCEP) at 16 weeks and diphenyl phosphate at 26 weeks of pregnancy were positively associated with gestational age and inversely associated with preterm birth. In female newborns, BCEP at 16 weeks was inversely related to birth weight and length z-scores. In male newborns, we observed negative associations of 26-week di-n-butyl phosphate with the ponderal index at birth. No mediation by the highest maternal blood pressure or glucose levels during pregnancy was identified. In this cohort, gestational exposure to some OPEs was associated with gestational age, preterm birth, and neonatal anthropometric measures. Certain associations tended to be window- and infant sex-specific. Graphical abstract: Image 1 Highlights: BCEP was positively associated with gestation age and inversely with preterm birth. DPHP was positively associated with gestation age and inversely with preterm birth. BCEP was inversely associated with birth weight and length z-scores in females. DNBP was inversely associated with the ponderal index at birth in males. Associations of OPEs and pregnancy outcomes might be window- and infant sex-specific.